2016
DOI: 10.1002/bsl.2218
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Release Placements of Insanity Acquittees in Oregon: 2012–2014

Abstract: Between January 1, 2012 and December 31, 2014, there was a large population (N = 200) of insanity acquittees placed on conditional release (CR) in the state of Oregon. This article looks at the demographic and system characteristics of this large group of individuals. The authors then focus on the initial housing placement and what happens to individuals after their release in relation to their housing placement. In Oregon, insanity acquittees are either conditionally released directly by the court or placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Overall, the rate of return to the hospital in the current sample (22%) was comparable to recent trends nationally (Novosad et al, 2016; Vitacco et al, 2014). Those who ultimately returned to the hospital were able to maintain community status for an average of nearly three years, indicating a period of successful transition before problems arose.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, the rate of return to the hospital in the current sample (22%) was comparable to recent trends nationally (Novosad et al, 2016; Vitacco et al, 2014). Those who ultimately returned to the hospital were able to maintain community status for an average of nearly three years, indicating a period of successful transition before problems arose.…”
Section: Discussionsupporting
confidence: 71%
“…Second, the current study is limited in that data regarding placement setting (e.g., group home, independent housing, family) were not available for those provisionally discharged to the community. Such factors could be controlled in subsequent research as there is some indication that placement type may be predictive of returns from conditional release (Marshall et al, 2014; Novosad et al, 2016) and, overall, more research is warranted on the impact of placement type on successful community reintegration. While risk communication was not the primary focus of the study, the data available in narrative-format reports was limited due to unscored items and inconsistent reporting of summary risk judgments and relevance ratings, which highlights the importance of clear, comprehensive report writing (Storey et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Supportive housing plays a particularly important role in maintaining the success of insanity acquittees in the community. Novosad, Banfe, Britton, and Bloom (2016) studied insanity acquittees released to different types of housing (e.g., independent apartments, secure residential facilities, family's homes), finding that individuals who are conditionally released to less structured settings have a higher rate of revocation back to the hospital. Salem et al (2015) found that individuals placed in independent housing following conditional release from the hospital were 2.5 times more likely to commit a new offense, nearly three times more likely to commit an offense against a person, and 1.4 times more likely to be readmitted for psychiatric treatment compared with individuals residing in supportive housing.…”
Section: Successful Transition To the Communitymentioning
confidence: 99%